Sprejemljivost jemanja ultranizkodozne oralne kontracepcije z 20 mikrog etinilestradiola in 75 mikrog gestodena med mladimi ženskami v multicentrični klinični raziskavi - Pinter, Bojana (Zdravniški vestnik, 2004)
Background. The acceptability of ultra low-dose oral contraception (OC) among young females after three and six cycles of treatment was assessed. Methods. In the clinical prospective study, carried out in 10 outpatient clinics in Slovenia, 240 healthy women aged 1630 years choosing ultra low-dose OC (20 microg ethinyl estradiol and 75 microg gestodene) were included. Results. The average age was 20.6 (+- 3.5) years. After three cycles (N = 228) there were no changes in body weight or blood pressure; one tenth (9.6%) of women reported irregular bleeding and 3.9% weight gain while other side effects occurred rarely. After three cycles 88.3% of the women initially included corztinued OC use (5% discontinued the use due to side effects). After six cycles (N = Z95) there were no changes in blood pressure; body weight statistically significantly increased for 0.5 kg providing the weight changes during the time were not considered. Fewer women reported side effects (3.6% irregular bleeding, 2.6% weight gain and rarely other side effects). After sixcycles 75.0% of the women initially included continued the OC use (7.5% discontinued the use due to the side effects). Conclusions. The study has shown good clinical acceptability of ultra low-dose OC by young females.
Keywords: Adolescenca; Adolescence; Adult; Adverse Effects; Blood Pressure; Body Weight; Contraceptives, Oral, Combined; Ethinyl Estradiol-Norgestrel Combination; Etinilestradiol-norgestrel, kombinacija; kontracepcija; Kontracipiensi kombinirani, oralni; Krvni pritisk; mlajše ženske; neželeni učinki; Odrasli; Prospective Studies; Prospektivne študije; tablete; Telesna teža